2020
DOI: 10.1039/d0mh00495b
|View full text |Cite
|
Sign up to set email alerts
|

Platinum single atoms on tin oxide ultrathin films for extremely sensitive gas detection

Abstract: Single atom Pt significantly improves the sensing performances of ultrathin SnO2 films for detection of triethylamine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
126
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 221 publications
(126 citation statements)
references
References 39 publications
0
126
0
Order By: Relevance
“…At present, the sensing mechanism of noble metal NPs or noble metal oxide particles modified SMOs has been extensively reported, and there are two main mechanisms that are widely accepted, that is Fermi‐level control [ 36,37 ] and oxygen spill‐over mechanism. [ 38,39 ] However, as the noble catalyst size reduced to atomic scale, because the electronic property of metal catalyst will change dramatically, it probably leads to variations in the sensing mechanism, which will be different from aforementioned acceptable mechanisms. But there are very few reports on the sensing mechanism of catalyst regulation at single atomic scale so far.…”
Section: Resultsmentioning
confidence: 99%
“…At present, the sensing mechanism of noble metal NPs or noble metal oxide particles modified SMOs has been extensively reported, and there are two main mechanisms that are widely accepted, that is Fermi‐level control [ 36,37 ] and oxygen spill‐over mechanism. [ 38,39 ] However, as the noble catalyst size reduced to atomic scale, because the electronic property of metal catalyst will change dramatically, it probably leads to variations in the sensing mechanism, which will be different from aforementioned acceptable mechanisms. But there are very few reports on the sensing mechanism of catalyst regulation at single atomic scale so far.…”
Section: Resultsmentioning
confidence: 99%
“…It essentially depends on the chemisorption reactions between acetone molecules and adsorbed active ions on the sensor surface, which cause a change in the charge depletion layer and regulate the change in resistance [ 46 , 47 ]. The interaction of oxygen molecules with the ZnS QDs sensor surface and ionic active site formation are summarized in Equations (5)–(7) [ 46 , 47 , 48 , 49 ]. …”
Section: Resultsmentioning
confidence: 99%
“…A large number of studies have shown that temperature and air flow rate have a great influence on the intensity of CTL [22][23][24][25][26][27]. Therefore, under the condition of keeping other conditions unchanged, we investigated the CTL intensity of trichloroethylene on the surface of PEG200/ZnO nanocomposite at different temperatures and air flow rate in order to obtain better response conditions, the specific results are shown in Fig.…”
Section: Effect Of Working Temperature Air Flow Rate and Analyte Conmentioning
confidence: 99%